Agricultural education in training of helpless childhood and adolescence of the 1930s in Paraíba: The case of pindobal (Research, Society and Development, 2021)
This article deals with an ongoing investigation about the Presidente João Pessoa Professional School (Pindobal) located in the municipality of Mamanguape in the State of Paraíba, founded in 1930. This investigation will address Agricultural Education (Mendonça, 2007) as the main pedagogical tool controlling male childhood and adolescence. The methodological approach is qualitative (Bogdan; Bikclen, 1999) and the analytical posture used is the Evidential Paradigm (Ginzburg, 1989) and the Micro-History (Vainfãs, 2002). The preliminary results that we found validate Pindobal as a correctional institution, destined to collect stray and delinquent minors to provide an useful education for the Brazilian and Paraíba State. The Brazilian State tried to found institutions for two types of Brazil: the Brazil of the working class and the poor, founding institutions such as Pindobal in the 20th century to attribute agricultural work as the only way of saving this population and Brazil of the ruling class, who founded an institution such as the Colégio do Caraça for the men of the future. Both institutions are austere and address the moralizing issue in its centrality, although one is aimed at the poor and the other aimed at the children of the ruling class.